Advanced electrical characterization of AlN/Si based heterogeneous junction for photonic applications. (February 2022) - Hassan, S.; Ahmed, S.; Ali, M.; Fahad, S.
Abstract: AlN/Si based heterogeneous junction is investigated, herein, for photonic applications. A hyperfine layer of AlN onto the n-type Silicon substrate is fabricated, and a detailed analysis of subject stack has been carried out by variety of techniques such as Scanning Electron Microscope (SEM), Current-Voltage (I–V), Capacitance-Voltage (C–V), Charge Deep Level Transient Spectroscopy (Q-DLTS), Transient of Photo-voltages (TPV) and Kinetics of Dark and Luminous Currents. The occurrence of Si3 N4 layer at the interface of AlN and Si has been witnessed and extensively studied by the electrical diagnostic approaches to identify a crucial role of the charges, which may directly affect the properties and operation of whole AlN/Si stack. The optical measurements have also been performed and evidence of Si3 N4 layer formation at the AlN and Silicon interface, which plays pivotal role to the overall AlN/Si stack. Furthermore, the defect levels and their respective qualitative as well as quantitative analysis near the valence and conduction band edges of AlN is also reported. The given stack has been investigated by multi-bias and switched voltage (positive/negative) routines at different active areas of subject AlN device matrix for their potential usage in Deep ultra-violet (DUV) and other photonic application.